2013
DOI: 10.1111/acfi.12029
|View full text |Cite
|
Sign up to set email alerts
|

Organisational and professional commitment of early career accountants: do mentoring and organisational ethical climate matter?

Abstract: This study assesses the effects of mentoring and organisational ethical climate (OEC) on the organisational and professional commitment (PC) of early career accountants (ECAs) (i.e. accounting graduate recruits with three or less years of working experience). The empirical data are based on a questionnaire survey from 86 ECAs in Australian public accounting firms, and hypothesis testing utilises partial least squares analysis. Our results indicate when a career development style of mentoring is adopted there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 98 publications
(145 reference statements)
1
29
0
2
Order By: Relevance
“…The instrument employs seven-point Likert-type scale (from "1" for strongly disagree to "7" for strongly agree), whereby the scale of 7 denotes organizational commitment of high level. The reliability and validity of for Mowday et al (1979), nine-item instrument have been reported by past works (Baack et al, 1993;Donnelly et al, 2003;Kwon and Banks, 2004;McManus and Subramaniam, 2014;Sommer et al, 1996;Steers, 1977). Appositely, the Cronbach alpha for this instrument was 0.864 in this study.…”
Section: Measures and Scalessupporting
confidence: 81%
“…The instrument employs seven-point Likert-type scale (from "1" for strongly disagree to "7" for strongly agree), whereby the scale of 7 denotes organizational commitment of high level. The reliability and validity of for Mowday et al (1979), nine-item instrument have been reported by past works (Baack et al, 1993;Donnelly et al, 2003;Kwon and Banks, 2004;McManus and Subramaniam, 2014;Sommer et al, 1996;Steers, 1977). Appositely, the Cronbach alpha for this instrument was 0.864 in this study.…”
Section: Measures and Scalessupporting
confidence: 81%
“…Findings also show that in every relationship among variables are consistent with previous research. As stated earlier, ethical work climate (McManus & Subramaniam, 2014;Tsai & Huang, 2008;Schwepker Jr., 2001) and perceived organizational support (Lew, 2009;Yew, 2011) are important antecedents of affective commitment. But the main point is that finding also shows that for affective commitment in social exchange perspective, perceived organizational support is the most important predictor to building commitment (Eisenberger, Fasolo, & Davis-LaMastro, 1990).…”
Section: Research Discussionmentioning
confidence: 90%
“…The participants had to indicate how much they agreed or disagreed with three statements (see Appendix) on a Likert scale, ranging from 1 (completely disagree) to 7 (completely agree). This reduced version of the scale of professional commitment has been used in previous studies, such as the one by McManus and Subramaniam (2014).…”
Section: Questionnaire and Measurement Of Variablesmentioning
confidence: 99%
“…One of the main reasons for the interest in studying OPC lies in the negative outcomes of this phenomenon. Most studies have found that OPC is associated with dysfunctional consequences, such as a reduction in job satisfaction, an increase in professional as well as organisational turnover intentions (Bamber & Iyer, 2002;Hall, Smith, & Langfield-Smith, 2005;Shafer, Lowe, & Fogarty, 2002), and damage to the quality of job performance (McManus & Subramaniam, 2014).…”
Section: Introductionmentioning
confidence: 99%